2020
DOI: 10.1186/s12939-020-1152-6
|View full text |Cite
|
Sign up to set email alerts
|

Utilization profile of emergency department by irregular migrants and hospitalization rates: lessons from a large urban medical center in Tel Aviv, Israel

Abstract: Background Irregular migrants (IMM) are excluded from the National health insurance in most developed countries and may use the emergency department (ED) as a source for medical care. This study aims to compare the use of ED by IM with that of Israeli citizens (IC) in a large urban hospital in Tel Aviv, including socio-demographic characteristics, hospitalization proportion and medical conditions on admission. Methods This cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…Patients seek ED care for urgent, life threatening issues, but at the same time, the ED is a routine source of primary care for many, and especially unserved patients. 38,39 Additionally, evidence shows that small percentages of patients accounts for the majority of ED visits. 40 Such variance requires risk stratification in order to find interventions to prevent revisits and to facilitate transitions to other care settings.…”
Section: Discussionmentioning
confidence: 99%
“…Patients seek ED care for urgent, life threatening issues, but at the same time, the ED is a routine source of primary care for many, and especially unserved patients. 38,39 Additionally, evidence shows that small percentages of patients accounts for the majority of ED visits. 40 Such variance requires risk stratification in order to find interventions to prevent revisits and to facilitate transitions to other care settings.…”
Section: Discussionmentioning
confidence: 99%
“…Referring to demographic characteristics, general factors, including gender, age, marital status, and education level, were found to be associated with health knowledge and attitude and thus affected migrants' HSU. Gender was found to be associated with both immigrants' (64,71,(87)(88)(89)(90)(91) and IMs' (12,13,17,50,55,(92)(93)(94) HSU; however, the association was mixed. Age also had a mixed effect on immigrants' (64,90) and IMs' (12-14, 38, 92, 95, 96) HSU.…”
Section: Predisposing Factorsmentioning
confidence: 92%
“…Gender was found to be associated with both immigrants' (64,71,(87)(88)(89)(90)(91) and IMs' (12,13,17,50,55,(92)(93)(94) HSU; however, the association was mixed. Age also had a mixed effect on immigrants' (64,90) and IMs' (12-14, 38, 92, 95, 96) HSU. Marital status was more frequently regarded as a protective factor for immigrants' (81, 89,97) and IMs' (13,14,17,50,55) HSU, while some articles reported that marital status had no influence on HSU by IMs (12,38).…”
Section: Predisposing Factorsmentioning
confidence: 92%
See 2 more Smart Citations